PENGEMBANGAN BĪ’AH LUGHAWIYYAH OLEH HIMPUNAN MAHASISWA JURUSAN PENDIDIKAN BAHASA ARAB DI IAIN PEKALONGAN - Rosyid, M Fairuz (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2020)
This article aims to develop the bÄ«'ah lughawiyyah carried out by the Student Association of the Arabic Language Education Institute of the State Islamic Institute of Pekalongan. This research focuses on the bÄ«'ah lughawiyyah model in terms of the purpose of the bÄ«'ah lughawiyyah, the forms of activities, and the learning model in the bÄ«'ah lughawiyyah. This research method is qualitative, using interviews, observation, and documentation techniques. Data were analyzed using Miles and Huberman analysis. The perspective in this study is the theory of language environment proposed by Stephen D. Krashen. The results of this study indicate that the development model of bÄ«'ah lughawiyyah based on "the purpose of learning about language," "learning languages" and "curricular objectives." The form of activities is in the way of learning module, nahwu sharaf study, bÄ«'ah lughawiyyah, ilqÄ' mufradÄt, MuhÄdatsah, Insya' monthly, language mading, rihlah lughawiyah, art and competition (PARBARA). There are three learning models, namely, student learning models with lecturers, student learning models with tutors and student and student learning models.